THE ROLE OF TASK UNCERTAINTY ON RELATIONSHIP BETWEEN KNOWLEDGE MANAGEMENT AND QUALITY OF BUDGET - Muhammad Ishak; Dedy Husrizal Syah (Proceeding International Conference on Information Technology and Business, 2016)
The report of BPK-RI’s Auditor results, can be concluded that any potential losses are more due to a weakness of apparatus’ skills and knowledge to manage the public financial, including the Government of Medan City. In addition, the lack of apparatus knowledge to realize a quality budget where the budget is marked by some of the characteristics of quality budget, namely the participation of the budget, the budget goal clarity, the adequacy of the budget, and feedback budget, which simultaneously that to the presence of task uncertainty.Through the participation of Medan City Government’s apparatus and to use the survey instruments, this study aims to provide the contribution of thought on the relationship between budget goal characteristics, task clarity, and knowledge management and to realize the knowledge management modeling as a continued step in the context of budgeting in Medan’s government area.Statistically, this research results showed that knowledge management has no effect on feedback budget (as one of four characteristics of quality budget) while the other characteristics (participation, budget goal clarity, and the adequacy of the budget), have an influence. To the problem of task uncertainty’s effect, only the adequacy of the budget that can not be influenced by the task uncertainty. Related to the problems of task uncertainty role as moderator of relationship between the budget and knowledge management, showed that there is no task uncertainty role as moderator between the knowledge management and feedback budget. KEY WORDS: knowledge management, characteristics of quality budget, and task uncertainty